Meningkatkan Kerja Sama Peserta Didik melalui Model Pembelajaran Student Teams Achievement Division (STAD) di Kelas IV SD Negeri 112/I Perumnas - Fenia Pranilsa; Roja Juita; Soleh Budiman (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
This research was conducted with the aim of increasing student cooperation in learning through the Student Teams Achievement Division (STAD) learning model in grade IV SD Negeri 112/I Perumnas. This research is a classroom action research (CAR) which discusses how teachers improve student cooperation through the Student Teams Achievement Division (STAD) learning model in grade IV SD Negeri 112/I Perumnas. The Student Teams Achievement Division (STAD) learning model that will be used in the research is conveying the goals and motivations of students, dividing students into small groups of 4-5 people heterogeneously, presenting learning information, the teacher giving assignments to group members to work on. together, the teacher guides group discussions, the teacher gives quizzes or questions for students, awards for the group that gets the highest score, and the teacher provides evaluations and conclusions. Collecting data in this study using observation. This research consisted of two cycles and each cycle consisted of two meetings. At each meeting there will be four stages, namely planning, implementation, observation and reflection. The results of the research in cycle one show that the Student Teams Achievement Division (STAD) learning model can improve student cooperation in class IV SD Negeri 112/I Perumnas. It can be seen from the results of observations in the first cycle that the presentation of the successful collaboration of students in class IV SD Negeri 112/I Perumnas is 66.14% with a sufficient predicate (C). In the second cycle the results increased to 75.76% with a good predicate (B).